Transient penile erection following lumbar puncture with intrathecal prophylaxis in primary testicular diffuse large B-cell lymphoma: a case report - Wang, Tao; Yang, Juan; Ma, Hongbing (Frontiers in Oncology, 2025)
Primary testicular diffuse large B-cell lymphoma (PT-DLBCL) is a rare and aggressive extranodal non-Hodgkin lymphoma that predominantly affects older men and carries a relatively high risk of central nervous system (CNS) relapse. Although lumbar puncture with intrathecal prophylaxis is commonly employed to reduce CNS involvement, transient penile erection after this procedure is extraordinarily rare. This case report describes a 51-year-old man diagnosed with PT-DLBCL (stage IA) who underwent right radical orchiectomy, followed by six cycles of R2-CHOP chemotherapy with intrathecal prophylaxis prior to each cycle. Approximately 30 minutes after the sixth lumbar puncture, the patient developed a transient penile erection that persisted for approximately three hours before resolving spontaneously without intervention. He later received additional cycles of R-HD-MTX and scrotal radiotherapy, and no further episodes of penile erection or disease recurrence were observed. This clinical vignette highlights the potential for rare neurogenic reflex erections associated with repeated lumbar punctures, underscoring the importance of heightened vigilance, procedural refinement, and close monitoring in patients receiving multiple intrathecal treatments.